Lineage-Specific Amino Acid Substitutions in Region 2 of the RNA Polymerase σ Subunit Affect the Temperature of Promoter Opening - Barinova, N. (American Society for Microbiology (ASM), 2008)
Highly conserved amino acid residues in region 2 of the RNA polymerase σ subunit are known to participate in promoter recognition and opening. We demonstrated that nonconserved residues in this region collectively determine lineage-specific differences in the temperature of promoter opening.